Development of Religious Activities for Science Teachers as an Effort to Integrate Islamic Values in Science Learning - Bakhrul Ulum; Nurlia Latipah (Universitas Pakuan, 2021)
This study aims to reveal the spiritual activities programmed by Madrasah Tsanawiyah Ja-alHaq for teachers, how Madrasah Tsanawiyah Ja-alHaq manages these activities, and the benefits of these activities for science learning in madrasas. This activity is carried out by interview technique. Data analysis was carried out by means of data reduction, data display, and conclusion drawing/verification. The results showed that the spiritual activities programmed for teachers at Madrasah Tsanawiyah Ja-alHaq included dhuha and zuhur prayers in congregation, reading sholawat, Asmaul Husna, reciting yanbu'a, monthly manaqib reading activities, recitation of the Taklim Almutaalim book and the matan salim taufiq book. These programs are determined based on the decisions of the teacher council meeting and coordination with the Ja-alhaq foundation management. To ensure the implementation of these activities, madrasah madrasas carry out monitoring and evaluation and make these activities one of the criteria for promotions or periodic salary increases for teachers. Through these activities, teachers are expected to increase their understanding of religious insight and be followed by improving the quality of worship. In teaching and learning activities for Science at Madrasah Tsanawiyah Ja-alHaq the teacher has been able to link the subject matter with the behavior of being grateful to Allah SWT for all the blessings given, the teacher also invites students to improve the quality of their worship by getting used to starting and ending learning by praying, and through learning Science students are invited to see the greatness and majesty of Allah SWT.